(untitled) (Journal of Pathology of Nepal, 2022)
Dedifferentiated chordoma is a rare variant of chordoma, exhibiting simultaneous presence of conventional chordoma and component of high grade sarcoma. It occurs either de novo or in the form of high grade transformation of a conventional chordoma in a setting of recurrence or radiotherapy induced changes. Despite similar clinical manifestations, it shows significantly poorer survival among all variants of chordomas, making an accurate diagnosis important. We, herein, report a case of large chordoma in a 65 years old female, arising de novo in sacrum, where dedifferentiated component was present only focally, highlighting the importance of adequate grossing.